Implementasi Program Badung Anti Kantong Plastik “BATIK” Berbasis Kearifan Lokal dalam Upaya Mengurangi Sampah Plastik di Kabupaten Badung (Studi Kasus di Desa Adat Sempidi, Kecamatan Mengwi, Kabupaten Badung) - Juniantari, Ni Made; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2020)
ABSTRACT Badung Anti Plastic Bag Program (BATIK) is an innovation program that aims to reduce single use plastic bags in Badung Regency according to the concept of local wisdom. The aim of this research is to find out the implementation of BATIK Program based on local wisdom in an effort to reduce plastic waste in Badung Regency, especially in Sempidi Village. This research is descriptive qualitative with observation, interviews, and documentation. The output of the research are based on an analysis with four implementation indicators of Edward III shows this program has not been implemented or running well because there are problems in indicators such as communication and outreach among the public are not optimal, lack of adequate budget and facilities, consideration to the addition of labor and wages and there is no absolute consequences regulations in the Sempidi Traditional Village. Keywords: Implementation, Badung Anti Kantong Plastik (BATIK), Sempidi Traditional Village.